Complications at usage of the new anticoagulant therapy at elderly patients - Trailov, Dunja; Despotović, Nebojša (Medicinski podmladak, 2021)
Introduction: New anticoagulant therapy (DOAC) was introduced a year ago. It is an alternative therapy for antagonists of vitamin K (VKA) in prevention and therapy of diseases with different etiology. Beside their advantages, bleeding stays a major complication. The fact is that there are no significant researches on this topic. Aims: To analyze the incidence of complications in patients treated with DOAC. Material and methods: We did a retrospective study including 60 patients who are older than 65 years with nonvalvular atrial fibrillation treated with anticoagulant therapy. Half of this number was taking DOAC (examined group) and half was taking VKA (control group). Apart from demographical and clinical parameters, I have also followed incidence, type and localization of bleeding. Results: In the group of patients who were taking DOAC, in 13.3% of cases bleeding occurred as a complication of therapy. Among them gastrointestinal bleeding was the most common (75%), but also hematomas on the body occurred (25%) and the therapy was immediately discontinued. In 45% of patients taking VKA bleeding was verified as a complication. From that number 33.5% had gastrointestinal bleeding and epistaxis, 8.6% hematomas and 24.4% hematuria. Comparing these two groups we can conclude that incidence of bleeding in the group taking DOAC was significantly lower than in the group taking VKA (p=0.038). Conclusion: In the examined group of patients older than 65, who were taking dabigatran, a significantly lower percentage of bleeding as a complication was noticed, compared to the control group taking VKA.